Replacing the involute profile with an improved cycloid profile to improve the bearing capacity for the elliptical gear drives : The elliptical gear drives - Thai, Nguyen Hong; Thom, Phung Van (Vietnam Journal of Science and Technology, 2024)
The involute curve is the most widely used in the design of tooth profiles for non-circular gears (NCGs) because of its mathematical simplicity and convenience for design and manufacture. Still, the condition to avoid undercutting often results in a large number of teeth and a small tooth size that reduces the load capacity of the gear drives. On the other hand, in elliptical gears (EGs), a particular case of NCGs, the unequal radii of the centrodes lead to unequal geometric shapes of the teeth arranged on the gear. To overcome the above phenomena and improve the load capacity of the gear drives in this study, the authors applied the improved cycloid profile as the tooth profile of the centered elliptical gear. The paper analyzes and evaluates to verify the disadvantages of tooth geometry of EG drives with the involute profile. On that basis, an improved cycloid curve is applied to improve the irregularity and increase the teeth size distributed on the gear. Two prototype gear drives with the same centrodes with ellipse involute and improved cycloid profiles were manufactured and experimental. The results showed that the EG drives with the improved cycloid profile allowed the design with fewer teeth than the involute profile to make the tooth size larger. Also, the experimental results showed that the practical versus theoretical gear ratio error value of the EG drives with improved cycloid profile and involute profile is 3.37% and 6.67%, respectively. It verified that the EG drives with the improved cycloid profile meshing process more smoothly than those with the involute profile. The research results are significant for applying and developing the improved cycloid profile in designing and manufacturing EG drives requiring high torque and precision.